2019
DOI: 10.1128/aac.01310-18
|View full text |Cite
|
Sign up to set email alerts
|

Drug Interactions between Dolutegravir and Artemether-Lumefantrine or Artesunate-Amodiaquine

Abstract: Across sub-Saharan Africa, patients with HIV on antiretrovirals often get malaria and need cotreatment with artemisinin-containing therapies. We undertook two pharmacokinetic studies in healthy volunteers, using standard adult doses of artemether-lumefantrine or artesunate-amodiaquine given with 50 mg once daily dolutegravir (DTG) to investigate the drug-drug interaction between artemether-lumefantrine or artesunate-amodiaquine and dolutegravir.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…(13)(14)(15)(16)(17)(18) Dolutegravir-based ART is being rapidly adopted as first-line HIV treatment; Dolutegravir is an HIV-integrase inhibitor reported to have minimal effects on CYP3A4 and a study has shown that DTGbased ART did not alter lumefantrine exposure significantly. (19,20) Additionally, no information is available on whether malaria or HIV disease may affect lumefantrine pharmacokinetics.…”
Section: Main Text (4116 Words) Introductionmentioning
confidence: 99%
“…(13)(14)(15)(16)(17)(18) Dolutegravir-based ART is being rapidly adopted as first-line HIV treatment; Dolutegravir is an HIV-integrase inhibitor reported to have minimal effects on CYP3A4 and a study has shown that DTGbased ART did not alter lumefantrine exposure significantly. (19,20) Additionally, no information is available on whether malaria or HIV disease may affect lumefantrine pharmacokinetics.…”
Section: Main Text (4116 Words) Introductionmentioning
confidence: 99%
“…This situation was seen with the antiretroviral dolutegravir. Licensed in 2013, it was shown to reduce viral load far more rapidly than comparator regimens 52 , to have a more favourable drug-drug interaction profile 53,54 , to be suitable for co-formulation with other antiretrovirals and potentially to incur fewer adverse effects 55 . Botswana made an early decision to transition national policy to use dolutegravir-based regimens as first-line, knowing that pregnancies would occur.…”
Section: Should Pregnant Women Be Considered 'Special' or 'Vulnerable': Non-maleficencementioning
confidence: 99%
“…If geographical PG data were easily and widely available, population-physiologically-based PK modelling could classify the same co-administration as contraindicated in some areas while recommended or neutral in others. Indeed, the recent availability of dolutegravir in LMICs may overcome some of these issues, as preliminary data reported no relevant clinical reduction of its concentration with standard doses of commonly used antimalarial regimens (as shown in Figure 2) [50].…”
Section: Pk and Pg Opportunitiesmentioning
confidence: 99%